2019
DOI: 10.1653/024.102.0129
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Development and Host Range of Crapemyrtle Bark Scale, Acanthococcus lagerstroemiae (Kuwana) (Hemiptera: Eriococcidae)

Abstract: The crapemyrtle bark scale, Acanthococcus lagerstroemiae (Kuwana) (Hemiptera: Eriococcidae), is an invasive pest of crapemyrtles, Lagerstroemia spp. L. (Lythraceae) in the southeastern USA. Information about its temperature-dependent development and host range is limited. The objectives of this study were to evaluate the effects of temperature on the immature development of A. lagerstroemiae, and to determine plant species suitable for immature development and reproduction. Developmental time and survival of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Crapemyrtle bark scale (CMBS; Acanthococcus lagerstroemiae Borchsenius, 1960) is a novel pest affecting crapemyrtles in the U.S. [7]. Biologically, A. lagerstroemiae is sexually dimorphic [8]. For most of its lifetime, the adult female is sessile on the bark [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Crapemyrtle bark scale (CMBS; Acanthococcus lagerstroemiae Borchsenius, 1960) is a novel pest affecting crapemyrtles in the U.S. [7]. Biologically, A. lagerstroemiae is sexually dimorphic [8]. For most of its lifetime, the adult female is sessile on the bark [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically, A. lagerstroemiae is sexually dimorphic [8]. For most of its lifetime, the adult female is sessile on the bark [8,9]. The insect secretes honeydew, which encourages sooty mold growth on the plants [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more plants beyond the loosestrife family (Lythraceae) and rose family (Rosaceae) to test, the more insights into the relationship between host suitability levels and host classification to obtain, which help uncover the main determinants of CMBS-host associations and better control CMBS. Even though 'Tiger' edible fig (Ficus carica) did not support nymphal CMBS's development and reproduction (Wang et al, 2019), we observed male pupae and gravid females of CMBS on 'Beer's Black' and 'Chicago Hardy' edible fig in a preliminary trial in 2018 (Fig. 1).…”
Section: Rapemyrtle Bark Scale [Cmbs (Acanthococcus Lagerstroemiae)mentioning
confidence: 61%